Doomscrolling dan Krisis Spiritualitas di Era Digital: Perspektif Kritis Seyyed Hossein Nasr - Hajidah Manaf, Ghina; Syafira, Luthfiati; Najaya, Arini; Syaifuddin, Helmi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
This study explores the phenomenon of doomscrolling, the habitual tendency to continuously browse negative news on social media, in relation to the increase in anxiety and the decline in mental well-being. This research employs Seyyed Hossein Nasr’s critical framework regarding concerning the impact of modern technology, including doomscrolling, on human spirituality in the digital era. Using a qualitative philosophical approach, supported by literature review and exploratory survey methods, the findings indicate that doomscrolling contributes to a spiritual crisis by distancing individuals from deep reflection and inner balance. Therefore, a more conscious and responsible approach to technology use is necessary to balance information consumption and spiritual well-being. Digital literacy education and awareness of doomscrolling’s adverse effects are essential steps in addressing this crisis.